Hybrid 20/23-G pars plana vitrectomy in endophthalmitis and trauma: a strategic approach. Issue 1 (January 2018) - Shroff, Daraius; Gupta, Priyanka; Gupta, Charu; Atri, Neelam; Dutta, Ranjan; Shroff, Cyrus
Purpose: To assess the safety and efficacy of hybrid vitreous surgery combining active 23-G ports with a sutured 20-G 6-mm infusion cannula for performing vitrectomy in endophthalmitis and trauma. Methods: This is a retrospective analysis of 10 eyes with endophthalmitis and 10 eyes with trauma requiring vitreous surgery, having corneal clarity suitable for vitrectomy and best-corrected visual acuity (BCVA) greater than or equal to light perception. All patients underwent hybrid 20/23-G vitrectomy. Intraoperative notes were analyzed for peroperative complications. The BCVA and retinal status at 3 months were analyzed. Results: In the endophthalmitis group, patients ranged from 5 to 85 years of age and showed varied etiologies. Retinal detachment was present in 5 eyes, which received silicone oil tamponade. Mean preoperative logMAR visual acuity (VA) was 2.29 ± 0.45, which improved to 1.10 ± 0.72 at 3 months postoperatively (p<0.001). Trauma cases ranged from 21 to 75 years of age. Retinal detachment was present in 9 out of 10 eyes, all of which received silicone oil tamponade. Preoperative logMAR VA was 2.26 ± 0.71, which improved to 1.33 ± 0.50 postoperatively (p<0.001). At 3 months postsurgery, the retina was attached in all eyes in both groups. Conclusions: The longer sutured 20-G cannula was easier to visualize through fibrin, exudates, and hemorrhage and did not slip out or enter the suprachoroidal space in any of our cases. The 23-G active ports and vitrectomy cutter enhanced safety and efficacy. Hybrid vitrectomy enabled safe surgery in these difficult cases.